Implementasi Program Pemantauan dan Evaluasi Kinerja Penyelenggaraan Pelayanan Publik (PEKPPP) di Puskesmas Jagir - Harsen, Rebecca Lorenzia; Priambodo, Bayu (IAI Nasional Laa Roiba Bogor, 2024)
Public services are one of the most important things needed by the community, one of which is health services. Health services in the city of Surabaya are considered inappropriate due to lack of communication between service providers and recipients, inadequate infrastructure facilities, and the use of digital technology is not optimal. Therefore, the government seeks to evaluate through the Public Service Implementation Performance Monitoring and Evaluation (PEKPPP) program in order to improve the performance of public service implementation. This study aims to find out and analyze the implementation of the PEKPPP program at the Jagir Health Center. This research method uses qualitative descriptive research through observation, interviews, and documents. The theory used is the theory of policy implementation by Edward III which consists of four variables, namely communication, resources, disposition, and bureaucratic structure. The results of the study show that the implementation of the Monitoring and Evaluation of Public Service Implementation Performance (PEKPPP) program at the Jagir Health Center can be said to be successful as a whole because it is able to improve the quality of public services through improving and improving the lack of supporting data. Where there is good communication between policy implementers and service users, adequate resources with their respective responsibilities in providing services, the disposition of human resources who provide full support for the implementation of the program, and a bureaucratic structure with a clear division of authority.